Tiquilia paronychioides (Phil.) A. T. Richardson (Boraginaceae): An ethnobotanical, ethnopharmacological, and toxicological review - Saldaña-Bobadilla, Vanessa; Ramirez, J-Kenedy; Perez-Chauca, Enma; Minchan-Herrera, Patricia (Ethnobotany Research and Applications, 2020)
Background: Medicinal plants have been used for many years in order to find new treatment strategies for various diseases. Peru is a country with a mega botanical diversity that promotes its use in traditional medicine and even in certain health establishments. Therefore, the purpose of this review is to analyze the information available on the traditional use, ethnopharmacology and toxicity of Tiquilia paronychioides (Phil.) A. T. Richardson; in addition to identifying possible research gaps to guide future studies of this plant. Methods: Scientific articles from databases such as PubMed, ScienceDirect, GoogleScholar, Scopus and thesis repositories from Peru were analyzed, with relevant information from Tiquilia paronychioides. The search terms were "Tiquilia paronychoides", "Tiquilia paronichioides" or "sand flower". Results: There is extensive information on the ethnobotany of this medicinal plant, however, there is little scientific evidence on the identification of bioactive components, pharmacological and toxicological aspects that support its traditional use. Conclusions: The available information on Tiquilia paronychioides was analyzed, structuring them in botany, traditional use, ethnopharmacology and toxicity. Scientific gaps were also identified on the pharmacological activities, chemical composition and toxicology of this plant species. Therefore, exhaustive studies of these aspects are necessary to guarantee the proper and safe use of the plant under review. Keywords: Boraginaceae; sand flower; ethnobotany; traditional medicine; complementary medicine; medicinal plants; Phytotherapy; Clinopodium revolutum.